Important Technical Considerations in Design of Battery Chargers of Electric Vehicles - Mahdi Bayati; Mehrdad Abedi; Maryam Farahmandrad; Gevork B. Gharehpetian; Kambiz Tehrani (Energies, 2021)
There are many important trade-offs and constraints on cost, volume, weight, conduction losses, switching losses, microcontrollers, isolation, voltage and current levels, voltage and current ripples, battery specifications, charging–discharging algorithms, control system, switch gate drivers, and efficiency of battery chargers in electric vehicles. In this paper, a well-known power electronic topology commonly used in recent relevant studies is considered, and some important technical considerations with regard to the mentioned trade-offs and constraints are discussed in detail for the first time. The discussion concerns the practical and theoretical experiences in implementation of battery chargers and charging stations of electric vehicles exclusively, and it can be extended to various other power electronic topologies.